Modeling and simulation to optimize cargo tank heating - Lim, Xiu Wen (2014)
High consumption of fuel oil concurrent with the increase in fuel pricing have prompted the research into optimizing the cargo oil heating process during marine transportation so as to maximize the efficiency of fuel oil consumption. Project started off with industrial collaboration with AET Tankers (Singapore) Pte Ltd to effectively manage the heat system in the ship.